FEASIBILITY OF INVESTMENT DEVELOPMENT SYUKURAN AMINUDDIN AMIR AIRPORT LUWUK - Hamzah; Fahira; Nirmalawati (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
Air transport in the town of Luwuk Banggai has increased significantly, this can be seen with increasing volume flight Syukuran Aminuddin Amir Airport average of 17.59% per year to various regions in the country and has the infrastructure facilities that can accommodate as many as 219261 average passengers/year with a percentage of 17.67% per year. The results of the research can be used to determine the feasibility of investing in the development of an airport by using economic calculation engineering and value advantage of the extension of the runway to 3000 m complete with other facilities with competing methods will be applied as follows: Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), and payback period. From the results of investment appraisal using the NPV method results obtained IDR.79,002,433,592.00 with methods derived into 36.142% IRR greater than 15% and Profitability Index (PI) has a value of 1.126 that is greater than 1 and analysis Payback Period (PP) was obtained within 15 years to reach the Break-Even Point.